The Study on Susceptibility to Temephos 1% sg of Aedes aegypti L. Larvae in Samutsakhon Province - ภวภูตานันท์, อนุสรณ์; เลาห์ประเสริฐ, ประชุมพร; แผ่พร, พรรณเกษม (Disease Control Journal, 2009)
The study aimed to examine the susceptibility of Aedes aegypti L. larva to Temephos 1% sg. The Samutsakhon strain and laboratory strain larva were prepared for testing which following the WHO standard recommendation (1981). The 5 concentrations of Temephos , 0.00125, 0.0025, 0.005, 0.01 and 0.02 mg/l, were prepared , the 25 larva were tested in each concentration and the test was replicated 4 times. The results showed that mortality of Samutsakhon strain and laboratory strain larva in each concentration of Temephos were not significantly different. The standard concentration at 0.02 mg/l , the Samutsakhon and laboratory strain larva had mortality rate of 99% and 100%, respectively.